MULAT: A study on the war on drugs campaign of former President Rodrigo Duterte - Anupol, Brian Martin J. (Animo Repository, 2022)
In 2016, President Rodrigo Duterte launched the War on Drugs to combat drug-related criminals and lessen the crime rates in the Philippines. Still, Duterte’s War on Drugs has embodied a system of violence and abuse that targeted the poverty-stricken individuals in the country. For this study, the researchers interviewed individuals who have experienced the war on drugs. Through the narrated personal experiences of the participants, the researchers were able to analyze the issue of the war on drugs and provide a deeper context to the societal problem by identifying the correlating factors that contributed to the system of the war on drugs. This research also provided a further understanding of the issue and the aftermath implications it has brought to the citizens of the country by producing a mini-documentary series where it served as a platform for the War on Drugs victims to share their experiences safely. The documentary series consists of three episodes to emphasize each participant’s story and give audiences ample time to fully grasp each victim’s story. The results of this study were able to present the readers and other future researchers with an in-depth analysis of the War on Drugs by the Duterte administration and deeper insights into how this systematic violent approach to combating the issue of drugs has heavily affected the citizens of the country and has a left a mark in the justice system of the Philippines.